2011
DOI: 10.1017/s1751731110001643
|View full text |Cite
|
Sign up to set email alerts
|

Estimating myostatin gene effect on milk performance traits using estimated gene content for a large number of non-genotyped cows

Abstract: The objective of this study was to estimate the myostatin (mh) gene's effect on milk, protein and fat yield in a large heterogeneous cow population, of which only a small portion was genotyped. For this purpose, a total of 13 992 889 test-day records derived from 799 778 cows were available. The mh gene effect was estimated via BLUP using a multi-lactation, multi-trait random regression test-day model with an additional fixed regression on mh gene content. As only 1416 animals, (of which 1183 cows had test-day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Crossbreeding between Bos taurus and Bos indicus is effective in increasing milk yield and its nutrient contents, such as protein, fat, and total solid. A study by Buske et al (2011) showed that the myostatin mutant gene was responsible for higher milk, protein, and fat yield in Belgian blue cows. Belgian blue have muscle hypertrophy (mh) that implicates higher milk production and reduced saturated fatty acid content in milk.…”
Section: Effect Of Breed On Cow Performance During Lactationmentioning
confidence: 99%
“…Crossbreeding between Bos taurus and Bos indicus is effective in increasing milk yield and its nutrient contents, such as protein, fat, and total solid. A study by Buske et al (2011) showed that the myostatin mutant gene was responsible for higher milk, protein, and fat yield in Belgian blue cows. Belgian blue have muscle hypertrophy (mh) that implicates higher milk production and reduced saturated fatty acid content in milk.…”
Section: Effect Of Breed On Cow Performance During Lactationmentioning
confidence: 99%
“…On the one hand, breeders of BBB used homozygous sires to increase the frequency of "mh" allele; thus, it is expected that nearly all BBB animals are mh/mh (Coopman, 2008; McPherron & Lee, 1997). On the other hand, it has been showed that the wild‐type allele of this gene (+) is responsible for a higher milk, protein and fat yields in DPBB cows; thereupon, currently the DPBB animals can be divided into three genotypes (+/+, +/mh and mh/mh) (Buske et al., 2010, 2011, 2011). Although it has been documented that milk produced by DPBB cows has a higher quality (e.g.…”
Section: Introductionmentioning
confidence: 99%